Promoting the Participation of Indigenous Peoples in Environmental Impact Assessment: Effectiveness of Akwé: Kon Guidelines in Finland - Onyango, Vincent; Wiman, Henri (European Scientific Journal, ESJ, 2021)
Indigenous peoples’ participation in public policy and planning is ascribed in numerous international and national legal instruments as essential to the realisation of their self-determination. This study examines how the Akwé: Kon guidelines (AK) can promote effective indigenous peoples participation in environmental management, especially during environmental impact assessment (EIA). Special focus is drawn on the Finnish context, home of the Sámi indigenous people. The study applies an effectiveness review package by Lee and Colley (1999), supplemented by interview and questionnaire surveys, to analyse how effective the AK have been. It was found that although they were useful in promoting further interaction of the Sámi with authorities, the AK did not address their most fundamental political and legal grievances. This leaves room for EIA policy and practice, in Finland and all other jurisdictions with indigenous peoples, to consider how they can more effectively harness the potentialities in AK.